Effectiveness and Safety of Carbamazepine versus Gabapentin in the Pharmacological Management of Trigeminal Neuralgia: Carbamazepine vs Gabapentin in Trigeminal Neuralgia - Jabbar, Maria; Akhtar, Uzair Bin; Akram, Komal; Khawaja, Mustafa Ayub; Khalil, Muhammad (Pakistan Journal of Health Sciences, 2025)
Carbamazepine is considered the first-line pharmacological therapy for trigeminal neuralgia (TN). Gabapentin, another antiepileptic drug, is increasingly used, but its role as a substitute for carbamazepine remains uncertain. Objectives: To compare the effectiveness and safety of gabapentin and carbamazepine in the management of trigeminal neuralgia. Methods: This prospective comparative study included 80 patients presenting to the Department of Oral and Maxillofacial Surgery at Sharif Medical and Dental Hospital from February 2023 to January 2024. Patients were divided into two groups of 40 each: Group A received gabapentin 300 mg twice daily, and Group B received carbamazepine 200 mg twice daily. Pain intensity was assessed using the Visual Analogue Scale (VAS), and frequency of attacks was recorded on the 3rd, 7th, and 15th days of follow-up. Side effects were also documented. Mann-Whitney U and Chi-square tests were used for statistical analysis, with p≤0.05 considered significant. Results: Group A exhibited lower median VAS scores compared to Group B at all follow-up intervals, with statistically significant differences on the 2nd and 3rd follow-ups. Although gabapentin demonstrated fewer adverse effects, carbamazepine showed the highest percentage of good therapeutic response based on reduced frequency of attacks. Conclusions: Both drugs are effective in managing trigeminal neuralgia. Carbamazepine provides superior pain relief and reduction in attack frequency, whereas gabapentin is associated with fewer side effects.